How do you solve this ?

(-a) 5 + (-a)3 = ???

The book says the result is 8 but how do you get to that ??

(3 and 5 a 'to the power'.shoud be above right bracket but dont know how to write it)

Results 1 to 4 of 4

- Dec 29th 2007, 10:07 AM #1MoondancerGuest

- Dec 29th 2007, 10:14 AM #2

- Dec 29th 2007, 10:14 AM #3
"8" is wrong, unless there's a typo.

First, we have that $\displaystyle (-a)^n = (-1)^na^n = -1 \cdot a^n$ when n is odd. So:

$\displaystyle (-a)^5 + (-a)^3 = -a^5 + -a^3$

The only thing I can think of to do from here is to factor it:

$\displaystyle = -a^2(a^2 + 1)$

By the way, to type powers without using LaTeX, use (-a)^5, etc.

-Dan

- Dec 29th 2007, 10:23 AM #4